Arginine metabolism and its protective effects on intestinal health and functions in weaned piglets under oxidative stress induced by diquat. Issue 11 (13th July 2017) - Zheng, Ping; Yu, Bing; He, Jun; Yu, Jie; Mao, Xiangbing; Luo, Yuheng; Luo, Junqiu; Huang, Zhiqing; Tian, Gang; Zeng, Qiufeng; Che, Lianqiang; Chen, Daiwen
Abstract: The intestine plays key roles in maintaining body arginine (Arg) homoeostasis. Meanwhile, the intestine is very susceptible to reactive oxygen species. In light of this, the study aimed to explore the effects of Arg supplementation on intestinal morphology, Arg transporters and metabolism, and the potential protective mechanism of Arg supplementation in piglets under oxidative stress. A total of thirty-six weaned piglets were randomly allocated to six groups with six replicates and fed a base diet (0·95 % Arg, ) or base diet supplemented with 0·8 % and 1·6 %l- Arg for 1 week, respectively. Subsequently, a challenge test was conducted by intraperitoneal injection of diquat, an initiator of radical production, or sterile saline. The whole trial lasted 11 d. The diquat challenge significantly decreased plasma Arg concentration at 6 h after injection ( P <0·05), lowered villus height in the jejunum and ileum ( P <0·05) as well as villus width and crypt depth in the duodenum, jejunum and ileum ( P <0·05). Oxidative stress significantly increased cationic amino acid transporter ( CAT )- 1, CAT-2 and CAT-3, mRNA levels ( P <0·05), decreased arginase II ( ARGII ) and inducible nitric oxide synthase mRNA levels, and increased TNF- α mRNA level in the jejunum ( P <0·05). Supplementation with Arg significantly decreased crypt depth ( P <0·05), suppressed CAT-1 mRNA expression induced by diquat ( P <0·05), increased ARGII and endothelial nitric oxide synthase mRNA levels ( P <0·05), and effectively relieved the TNF- α mRNA expression induced by diquat in the jejunum ( P <0·05). It is concluded that oxidative stress decreased Arg bioavailability and increased expression of inflammatory cytokines in the jejunum, and that Arg supplementation has beneficial effects in the jejunum through regulation of the metabolism of Arg and suppression of inflammatory cytokine expression in piglets.